Microalgae-cyanobacteria–based biostimulant effect on salinity tolerance mechanisms, nutrient uptake, and tomato plant growth under salt stress - Mutale-joan, Chanda; Rachidi, Farid; Mohamed, Hachimi Alaoui; Mernissi, Najib El; Aasfar, Abderrahim; Barakate, Mustapha; Mohammed, Danouche; Sbabou, Laila; Arroussi, Hicham El (Journal of applied phycology, 2021)
High soil salinity is a major abiotic stress affecting the growth, nutrition, development, and productivity of crops. This study investigated the modulating effect of combined microalgae-cyanobacteria extract formulations (MEF1%, MEF5%, and MEF10%) prepared from the species Dunaliella salina , Chlorella ellipsoidea , Aphanothece sp., and Arthrospira maxima , on tomato plant growth and tolerance under four NaCl concentrations (0, 80, 120, and 150 mM). MEF5% enhanced the vegetative growth of tomato plants, characterized by higher shoot and root weight and larger leaf area. According to principal component analysis (PCA), improved plant growth was closely associated with leaf photosynthetic pigments, which was mainly due to improved osmotic adjustment and ion homeostasis. Proline accumulation was significantly enhanced by MEF5%-treatment in plants grown under 120 mM and 150 mM NaCl conditions. MEF5%-treatment also significantly improved nitrogen (N), phosphorus (P), and potassium (K + ) absorption in plants grown at 80 mM and 120 mM NaCl levels. Leaf lipid peroxidation through ROS oxidative stress significantly decreased with enhanced CAT and SOD activities in MEF5%-treated plants. MEF5% triggered a significant decline in fatty acid content, indicating fatty acid transformation into other lipid forms such as alkanes, which are essential in the cuticular wax synthesis of hydric stressed plants. Enhanced K + uptake and reduced Na + /K + ratio in the leaves of treated plants indicate MEF’s active role in reestablishing ion homeostasis. Nutrient uptake can be improved by enhanced root biomass, which subsequently increases the roots’ surface for nutrient absorption. These results indicate that MEF stimulated plant growth and tolerance responses through (i) enhanced antioxidant enzyme activities and (ii) improved root growth and nutrient uptake. Therefore, combined microalgae-cyanobacteria formulations could be another sustainable alternative to boost nutrient uptake, growth, and crop adaptability under normal and saline conditions.